PREPARING FUTURE LEADERS OF THEIR RACES -THE POLITICAL FUNCTION OF CHILDREN’S CHARACTERS IN CONTEMPORARY AFRICAN AMERICAN PICTURE-BOOKS - Klęczaj-Siara, Ewa (Journal of Education Culture and Society, 2019)
Aim. The aim of the article is to analyse the ways African American children’s characters are constructed in selected picture-books and to determine whether they have any impact on the conduct of contemporary black youth facing discrimination in their own lives. It also argues that picture-books are one of the most influential media in the representation of racial problems.Methods. The subjects of the study are picture-books. The analysis pertains to the visual and the verbal narrative of the books, with a special emphasis being placed on the interplay between text and image as well as on the ways the meaning of the books is created. The texts are analysed using a number of existing research methods used for examining the picture-book format. Results. The article shows that the actions of selected children’s characters, whether real or imaginary, may serve as an incentive for contemporary youth to struggle for equal rights and contribute to the process of racial integration on a daily basis.Conclusions. The results can be considered in the process of establishing educational curricula for students from minority groups who need special literature that would empower them to take action and join in the efforts of adult members of their communities.